The Sedekah Rame Tradition as Social Capital for Strengthening Community Food Security: A Contribution to Achieving the Sustainable Development Goals (SDGs) - Ivana; Munir; Cholidah Utama (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to analyze the Sedekah Rame tradition as social capital rooted in Islamic values in strengthening food security among agrarian communities in Lahat Regency, as well as its contribution to the achievement of the Sustainable Development Goals (SDGs). Theoretical Framework: The study employs social capital theory (Putnam and Bourdieu), cultural da’wah, solidarity-based Islamic economics, and the lived Islam perspective to understand the socio-religious functions of Sedekah Rame in community life. Literature Review: Previous studies highlight the importance of local Islamic traditions in maintaining social harmony; however, research linking local religious practices to food security and the SDGs remains limited. Methods: This study employs a qualitative approach using ethnographic methods through participant observation, in-depth interviews with traditional leaders, religious figures, farmers, and village officials, as well as documentation analyzed interactively. Results: Findings indicate that Sedekah Rame functions as social capital that strengthens trust, solidarity, mutual aid, and mechanisms for redistributing harvests. This practice supports household and community food security through the strengthening of social networks, food access, and community participation. Implications: These findings suggest that local Islamic traditions can serve as community-based development strategies that support sustainable food security and social resilience. Novelty: This study offers a new perspective by positioning Sedekah Rame as Islamic social capital that functions in food redistribution and the strengthening of community food security, as well as contributing to the achievement of SDG 2 (Zero Hunger), SDG 11 (Sustainable Cities and Communities), and SDG 17 (Partnerships for the Goals).